تثمير الأملاك الوقفيّة في ظلِّ قانون الأوقاف رقم:91-10 (El-Wahat Journal for Research and Studies, 2023)
مُلخص: لضمان استمرار تأدية الملك الوقفيّ للغرض الذي أُنشئ من أجله حرص المشرّع الجزائريّ أن يضمَّ قانون رقم: 01-07 المعدل والـمتمم للقانون الأوقاف رقم: 91-10 صيَّغا تثميرية عديدة تتماشى مع أي وعاء وقفيّ حسب طبيعة نمائه، ولتسليط الضوء على هذا الجانب استهدفت الدِّراسة بيان نموذج من عقود خاصّة، نظم المشرّع أحكامها في نصوص تشريعيّة على شكل آلية لتثمير الأملاك الوقفيَّة سواء أكانت فلاحيَّة أم مبنيَّة أو قابلة للبناء، إلاَّ أنَّ المشرّع لم يسلك في تقريرها مسلك التفصيل في عرض ضوابط تطبيقها وتحديد آثارها، وهو الأمر الذي يستلزم الرجوع إلى أحكام الشريعة الإسلاميّة لاستدراك ذلك، طبقا لنصّ المادّة الثانية للقانون الأوقاف رقم: 91-10.     كلمات دالة: تثمير أملاك وقفيّة، عقد مساقاة، عقد مزارعة، عقد حكر، عقد مرصد.       Abstract: Aiming at ensuring the ongoing mission of waqf facilities, the Algerian legislator included in the law No. 01-07, modifying and completing Waqf Law No. 91-10, different possible investment forms relevant to different waqf types. For further consideration, this study sheds light on the special contracts' type. The Algerian legislator issued legislative texts, comprising the judgments of this type of waqf, under a shape of a mechanism of investing waqf facilities, being it agricultural, founded or for prospective construction. However, the legislator did not consider it in its details, especially its application criteria and specification of its impacts. Therefore, it is inevitable to take the judgments of Islamic Shari'a as a reference to make up the legal vacuum in compliance with the article No. 02 of Waqf Law No. 91-10.Key words: investment of Waqf Facilities, Muzara'a contract, Musakat contract, Hikr contract, Mersad contract.